2022
DOI: 10.19053/01228420.v19.n3.2022.14685
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Bacillus thuringiensis and Bacillus pumilus potential biological control agents of the coffee berry borer under field conditions of Puerto Rico

Abstract: Field trials were conducted in two years to evaluate persistence of B. thuringiensis and Bacillus pumilus under field conditions. Strains of B. thuringiensis (3971) and B. pumilus (4185) were isolated from coffee agro-ecosystem in Puerto Rico. Field trials consisted in plots of nine coffee trees arranged in a randomized complete block design, sprayed with Bt-3971 and Bp-4185 at 108, 109, or 1010 colony forming units CFU ml-1 or non-inoculated. In year 1, B. thuringiensis and B. pumilus survived up to six month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Sutto-Ortiz et al ( 2017) and Bacame-Valenzuela et al (2015) reported the isolation of thermotolerant actinomycetes and fungal strains capable of synthesizing enzymes of industrial interest, such as phospholipase A and feruloyl esterases, respectively. Additionally, Camacho-Ruiz et al (2020) reported the isolation from Sonoran Desert soils of Streptomyces, Bacillus, Aspergillus, and Aureobasidium strains able to produce gastrointestinal lipase inhibitors. Moreover, Baqueiro et al (2019) reported the biotechnological potential of Bacillus strains capable of producing stable proteases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sutto-Ortiz et al ( 2017) and Bacame-Valenzuela et al (2015) reported the isolation of thermotolerant actinomycetes and fungal strains capable of synthesizing enzymes of industrial interest, such as phospholipase A and feruloyl esterases, respectively. Additionally, Camacho-Ruiz et al (2020) reported the isolation from Sonoran Desert soils of Streptomyces, Bacillus, Aspergillus, and Aureobasidium strains able to produce gastrointestinal lipase inhibitors. Moreover, Baqueiro et al (2019) reported the biotechnological potential of Bacillus strains capable of producing stable proteases.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the endospore suspension was added with 10% (w/v) of maltodextrin as a carrier ( Bhagwat et al, 2020 ; Vignesh et al, 2022 ) and dried using a laboratory spray dryer (Yamato ADL3115) at 110°C and 75°C as inlet and outlet air temperature, respectively, obtaining a fine powder containing around 1 × 10 8 endospores/g. Endospores were quantified, resuspending the powder in water and employing two methods: (a) using a Newbauer chamber (40X); (b) by plate count, according to Bolanos-Carriel and Vazquez Soto (2022) method. Endospores morphological and wall characteristics were verified through the application of the Endospore Stain Protocol, recommended by the American Society for Microbiology ( Hussey and Zayaitz, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation